A traceable authentication system based on blockchain for decentralized physical infrastructure networks - Liang Liu; Kazumasa Omote (Scientific Reports)
Abstract With the rapid development of decentralized physical infrastructure networks (DePIN), resource sharing among devices has become more convenient, but it also introduces new risks of malicious behavior. Attackers may evade accountability by frequently switching accounts, making authentication and traceability essential. However, existing approaches face limitations in scalability, cost, and privacy, rendering them unsuitable for large-scale DePIN environments. To address these challenges, this paper proposes a traceable authentication system that integrates government public key infrastructure with blockchain technology. The system leverages government-issued electronic identity cards to generate digital signatures and employs smart contracts to automate the authentication process. Physical infrastructure (PI) devices can directly retrieve authentication results from smart contracts, enabling efficient and secure authentication. Moreover, the immutable logs recorded on the blockchain provide reliable evidence for tracing a user’s unique real-world identity. Performance evaluation results demonstrate that the system reduces authentication costs by up to 40% and achieves high throughput under both RSA and ECDSA algorithms. The contributions lie in enhancing the scalability of DePIN authentication, preserving user privacy, and enabling real-world traceability.